Liability of Freight Forwarding Companies for Losses on Delivery of Fishery Products Due to Container Shortage Effects - Kamaluddin, Muhammad Aqil; Chumaida, Zahry Vandawati (Media Iuris, 2025)
Nowadays various types of transportation are also used in the context of Indonesia’s development, one of which is the sea transportation service business or better known as freight forwarding. However, there has been a decline in export products which cannot be separated from the impact of containers shortage. Previously, the impact of container shortages often occurred, but only for a short time. However, a long-term containers shortage only occurred when the COVID-19 pandemic emerged. With the effects of a shortage of containers, this was exacerbated by other problems such as limited space on logistics carriers which can affect the domestic logistics distribution supply chain. This research uses a normative legal research approach with the results indicating that the party responsible in cases of losses due to containers shortage is the freight forwarding company and the legal consequence of a transportation agreement that is affected by containers shortage is that as long as the carrier has agreed to the transportation agreement, the freight forwarding company must ensure that containers are available according to the transportation agreement. The reason for the shortage of containers can be used as a justification for the carrier’s actions but not in the long term.